Scale-Up Design & Safety Analysis Of Palm Kernel Oil Extraction Using Supercritical Carbon Dioxide System - Sofian, Asmah Mohamed (Universiti Sains Malaysia, 2020)
In recent years, supercritical carbon dioxide technology has been widely used as an alternative extraction method. However, improper plan in upscaling can lead to inefficient process and hazards. Therefore, the objective of the study is to focus on the layout of using the scale-up criteria for the principle of similarity in upscaling and the safety analysis as a preliminary assessment for a large scale that would highly be beneficial for future works. Four dimensionless groups were selected and calculated as the suitable scale-up criteria by relevancy evaluation and expert system, as constant mfmB gave the highest strength, while dpdint had the lowest with 7.488 and 3.98, respectively. Constant combination of mfmB & Re was the best criteria for 0.57 L – 50 L scale during the scale-up simulation due to the highest total fast extraction rate and kf, while for 40 ML – 50 L scale, the lowest was obtained from constant dpdint and constant Re. The safety assessment of the system was evaluated by fault tree analysis where 25 minimal cut sets led to overpressure mainly caused by leakage of the piping and connector. The calculated top-level failure probabilities for probabilities analysis and Monte Carlo simulation were 1.241485×10−1 and 1.237203×10−1 respectively.